Peran peron dalam pemasaran kelapa sawit di kecamatan rambah hilir kabupaten rokan hulu - Manalu, Bukit Tua (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
Purpose of this research to find out the marketing channel and the role of the platform palm oil marketing in Kecamatan Rambah Hilir. Method of collecting the data was using questioner, interview, and dokumentation. Samples were sixty person taken in a random from all of smallholders to sell their crops to the platform. Questioner data got and tested with validity and reliability and very a role. The result of the research showed that the role of the platform in Kecamatan Rambah Hilir was sufficient a role. M arketing channel did by farmer in Kecamatan Rambah Hilir subdictrict was middleman, platform and palm oil mill. So that marketing channel often used by farmer to sell their income is platfoerm, then the role of platform on palm oil marketing in Kecamatan Rambah Hilir can increase the farmer income because got TBS price higher if compared with farmer sell palm iol to middleman. The existence of platform in Kecamatan Rambah Hilir may helped farmers economic and increase the welfare of farmer in the future.Keywords : Palm oil, Peron, Role